2018
DOI: 10.1021/acs.jpcc.8b08131
|View full text |Cite
|
Sign up to set email alerts
|

Band Structures of Periodic Porphyrin Nanostructures

Abstract: Recent progress in the synthesis of π-conjugated porphyrin arrays of different shapes and dimensionalities motivates us to examine the band structures of infinite (periodic) porphyrin nanostructures. We use screened hybrid density functional theory simulations and Wannier function interpolation to obtain accurate band structures of linear chains, 2D nanosheets and nanotubes made of zinc porphyrins. Porphyrin units are connected by butadiyne (C4) or ethyne (C2) linkers, or "fused" (C0), i.e. with no linker. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Figure 5 shows typical shapes-various porphyrin nanowires, nanotubes, and nanosheets. Posligua et al [61] studied the band structures of porphyrin nano sheets and tubes formed through covalent linkers. They used screened hybrid density functional theory simulations and Wannier function interpolation to obtain accurate band structures.…”
Section: Porphyrins As Nano Wires Sheets Tubes and Laddersmentioning
confidence: 99%
“…Figure 5 shows typical shapes-various porphyrin nanowires, nanotubes, and nanosheets. Posligua et al [61] studied the band structures of porphyrin nano sheets and tubes formed through covalent linkers. They used screened hybrid density functional theory simulations and Wannier function interpolation to obtain accurate band structures.…”
Section: Porphyrins As Nano Wires Sheets Tubes and Laddersmentioning
confidence: 99%
“…Template‐assisted macrocyclization has most recently been applied to the preparation of tube‐shaped, ball‐shaped, caterpillar‐like, and Russian doll‐like supramolecular assemblies. The evaluation of aromaticity in porphyrin nanoring systems, as well as the preparation of heterometalated porphyrin nanorings through the site‐selective demetalation–metalation strategy, are also hot topics in this area.…”
Section: Angle‐strained Alkyne‐containing π‐Conjugated Macrocyclesmentioning
confidence: 99%
“…Recent computational studies on infinite and discrete porphyrin nanotubes demonstrated that their electronic properties exhibit strong variations with the number of linking carbon atoms (C 0 /C 2 /C 4 ), [91] and nanotube diameter. [92] Density function theory (DFT) calculations (B3LYP/6-31G* with Grimme's D3 dispersion correction) were conducted to provide insight into the geometry and electronic structure of the porphyrin nanotubes discussed above.…”
Section: Molecular Modeling and Electronic Structure Calculationsmentioning
confidence: 99%